Photon‐Quantitative 6π‐Electrocyclization of a Diarylbenzo[b]thiophene in Polar Medium. Issue 8 (12th June 2015) - Li, Ruiji; Nakashima, Takuya; Galangau, Olivier; Iijima, Shunsuke; Kanazawa, Rui; Kawai, Tsuyoshi
Abstract The high reactivity of 6π‐electrocyclization in polar solvents has remained one of the important challenges for diarylethenes because of the emergence of a twisted intramolecular charge transfer (TICT) state at the excited state in such polar media, which usually quenches the photocyclization reaction. Herein we report on the preparation and highly efficient photocyclization of 2, 3‐diarylbenzo[b]thiophenes with nonsymmetric side‐aryl units in a polar solvent. While the dithiazolylbenzo[b]thiophene showed a suppressed quantum yield of 6π‐electrocyclization of 54 % in methanol, the replacement of a thiazole unit with a thiophene ring led to a photon‐quantitative 6π‐cyclization reaction. The nonsymmetrical modification into the side‐aryl units was considered to enhance the CH/π interactions between side‐aryl units to support a photoreactive conformation in methanol. The stabilization of the photochromic reactive conformation is expected to suppress the formation of the TICT state at the excited state, leading to highly efficient photoreactivity.